Daily Accumulation and Impacts of Marine Litter on The Shores of Selayar Island Coast, South Sulawesi - Roni Hermawan; Ario Damar; Sigid Hariyadi (Waste Technology, 2017)
West coast of Selayar facing solid marine litter during west monsoon period December until March, marine litter come from floating litter, carried by sea surface current and deposited along the west coast. Marine litter deposited on the west coast affected social, economic and ecological. This study aims to determine type, weight, density and distribution of marine litter; the impact of litter on water quality; the impact of economic, social and environmental ecosystems. Retrieved data using line transect at 7 observation points. Litter size were observed (> 2.5 cm) or macro litter. Floating litter and daily incresing of litters were also analyzed. Inorganic waste density is 14.3 ± 2.97 items/m2 for the number of pieces and 564.8 ± 196.1 g/m2 for waste weight. Daily accumulation was about 1 445 ± 1 743 g/m/day, the number of pieces 14.3 ± 8 item/m/day, cubication 0.0187 ± 0.019 m3/m/day. The impacts on seagrass and biota such as broken leaves, crushed and organism rafting on floating litter some types of coral such as Favia fragum, types of crustaceans such as Balanus. sp, Lepas. sp, Dosima. sp which affect the bio-diversity.